Excuses in Physical Education Made by Primary School Pupils of Fourth and Fifth Class - Vesna Štemberger (Karolinum Press, 2015)
Excuses in Physical Education Made by Primary School Pupils of Fourth and Fifth Class Researches show that children are mostly active at gym/sport in the school. So it is extremely important that they participate in physical education and aren't making excuses or aren't passive. Excuses for physical education were in the Slovenian area already a subject to a number of researches; however all deal with pupils in third triad and/or high school pupils. This research is the first of its kind dealing with younger pupils. Despite the fact that participation in physical education is a duty and right of every pupil, some pupils in physical education do not want to participate. Therefore, we wanted to find out how much and in what way the pupils of fourth and fifth class are making excuses for physical education. In the sample 319 pupils of fourth and fifth class were included. We found that absences of school children were within the expected range, because most children aren't long-term ill. Young pupils are expected to make excuses less often than older pupils, because the need for physical movement in this period is strongly expressed. When pupils excuse, this is most often due to illness or because of unsuitable premises and lack of time for personal hygiene after hours of physical education. Pupils in the case of non-participation in physical education often tell teacher the real reason, but often also bring an apology from parents. When pupils don't participate in physical education, they mainly observe it; less frequently the teacher finds another occupation for them. Omluvy z tělesné výchovy žáků čtvrtých a pátých tříd základní školy Výzkumy ukazují, že ve škole jsou děti nejaktivnější v tělocvičně - při sportu. Je tedy velmi důležité, aby se účastnily tělesné výchovy, tj. neomlouvaly se a nebyly pasivní. Omluvy z tělesné výchovy již byly na území Slovinska předmětem mnoha výzkumů, nicméně všechny se zabývaly středoškoláky. Tento výzkum je prvním svého druhu zabývající se mladšími žáky. Navzdory faktu, že účast v tělesné výchově je povinností a právem každého žáka, někteří se tělesné výchovy účastnit nechtějí. Proto jsme chtěli zjistit, jak často a jakým způsobem se žáci čtvrtých a pátých tříd omlouvají z tělesné výchovy. Do vzorku bylo zahrnuto 319 žáků čtvrtých a pátých tříd. Zjistili jsme, že absence žáků byla v očekávaném rozsahu, neboť většina dětí nebývá dlouhodobě nemocná. Od mladších žáků jsme očekávali méně omluv než od žáků starších, protože je potřeba tělesného pohybu v tomto období silná. Nejčastějším důvodem absence bývá nemoc, nevyhovující prostory a nedostatek času na osobní hygienu po hodinách tělesné výchovy. V případě neúčasti v tělesné výchově žáci často řeknou učiteli skutečný důvod absence, často také přinesou omluvenku od rodičů. Když se žáci tělesné výchovy neúčastní, většinou ji pozorují; méně často je učitelé zaměstnávají dalšími činnostmi.